Antibacterial Activities of Fungal Endophytes from Philippine Endemic Plant Dillenia philippinensis: Antibacterial Activities of Fungal Endophytes from Dillenia philippinensis - Española, Seraphim Marie; Resurreccion, Maria Criselda; Espiritu, Llewelyn (Journal of Tropical Life Science, 2023)
Fungal endophytes represent a group of microorganisms that establish symbiotic associations with plants and hold significant ecological importance. Their ability to produce a diverse array of biologically active secondary metabolites has garnered considerable interest in the search for novel drug leads. In this study a total of 33 fungal endophytes were isolated from leaf specimens of the Philippine endemic tree Dillenia philippinensis (Rolfe). The morphological characterization of the fungal isolates revealed their taxonomic affiliation with the following eight genera: Alternaria sp., Aspergillus sp., Geotrichum sp., Guignardia sp., Nigrospora sp., Paecilomyces sp., Pestalotiopsis sp., and Phialophora sp. A representative set of 22 fungal endophyte isolates was selected from the pool of isolates and subjected to large-scale cultivation, followed by extraction of their bioactive metabolites through liquid-submerged fermentation. The resulting crude extracts were evaluated for their inhibitory potential against two Gram-positive bacteria, namely Staphylococcus aureus and Methicillin-resistant Staphylococcus aureus (MRSA); and two Gram-negative bacteria, namely Escherichia coli and Multi-drug resistant Pseudomonas aeruginosa (MRPA), using the disc diffusion assay. The results indicate that the crude extracts obtained from endophytic fungi colonizing D. philippinensis represent a promising source of bioactive metabolites that exhibit noteworthy inhibitory activity against S. aureus, E. coli, and MRSA, with an effective concentration of 10 mg/mL. This study demonstrates that the fungal endophytes associated with Dillenia philippinensis foliage represent a rich source of bioactive metabolites with significant inhibitory activity against Gram-positive and Gram-negative bacteria. These lead to exploring the potential of these fungal endophytes as a viable source of novel therapeutics.